2008
DOI: 10.1677/joe-08-0260
|View full text |Cite
|
Sign up to set email alerts
|

Renal haemodynamic and tubular actions of urotensin II in the rat

Abstract: Urotensin II (UTS) is a potent vasoactive peptide that was originally identified in teleost fish. Mammalian orthologues of UTS and its receptor (UTSR) have been described in several species, including humans and rats. We have shown previously that bolus injections of UTS caused a decrease in urine flow and sodium excretion rates in parallel with marked reductions in renal blood flow (RBF) and glomerular filtration rate (GFR). The aim of this study was to determine the effect of UTS infusion at a dose that has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 33 publications
0
27
3
Order By: Relevance
“…Rat UII infusion rates (0.6 pmol or 6 pmol⅐min Ϫ1 ⅐100 g body wt Ϫ1 ) were chosen, on the basis of earlier studies in our laboratory (1,30), to induce modest, physiologically relevant changes in plasma UII concentrations with no accompanying alterations in systemic blood pressure. This aim was achieved as rUII infusion had no effect on mean arterial pressure (MAP) at either dose in both SHR (P treatment ϭ 0.47) and WKY (P treatment ϭ 0.41) rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat UII infusion rates (0.6 pmol or 6 pmol⅐min Ϫ1 ⅐100 g body wt Ϫ1 ) were chosen, on the basis of earlier studies in our laboratory (1,30), to induce modest, physiologically relevant changes in plasma UII concentrations with no accompanying alterations in systemic blood pressure. This aim was achieved as rUII infusion had no effect on mean arterial pressure (MAP) at either dose in both SHR (P treatment ϭ 0.47) and WKY (P treatment ϭ 0.41) rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern of distribution is in agreement with our observations of the profound effects of UII on renal hemodynamic and tubular function in the rat in vivo. UII administration caused a marked reduction in glomerular filtration rate (GFR) which was accompanied by an antidiuresis and antinatriuresis (1,30). Other groups (24,36) reported somewhat different effects, perhaps reflecting different doses and/or routes of UII administration, but nonetheless showed that UII can influence both glomerular filtration and tubular sodium reabsorption.…”
mentioning
confidence: 99%
“…Both unglycosylated (w42 kDa) and glycosylated (w60 kDa) forms of UTR protein have been identified in human adrenocortical tissues and COS-7 cells overexpressing UTR (Boucard et al 2003, Giuliani et al 2009). Ventricular samples from rats express the unglycosylated form of UTR, whereas the glycosylated form was the only immunoreactive UTR protein identified in rat kidneys, coronary arteries, and cultured coronary artery smooth muscle cells (Gong et al 2004, Abdel-Razik et al 2008b, DominguezRodriguez et al 2012. In this study, we found that newborn pig renal afferent arterioles express both unglycosylated and glycosylated forms of UTR.…”
Section: Discussionmentioning
confidence: 99%
“…injection of iron into rats and mice resulted in iron-induced free radical injury and cancer in the kidney. 46 Renal tissue Ang II concentration has been reported to be 5.8 nmol kg -1 kidney wt, 47 which is two orders higher than the serum Ang II level. First, we analyzed whether Ang II treatment increases intracellular iron concentration.…”
Section: Effect Of Ang II On Iron-transporting Protein S Tajima Et Almentioning
confidence: 97%